Best proximity point theorems for α-nonexpansive mappings in Banach spaces - Kong, D.; Liu, Lishan; Wu, Yong Hong (Springer International Publishing, 2015)
In this paper, we discuss sufficient and necessary conditions for the existence of best proximity points for non-self-a-nonexpansive mappings in Banach spaces. We obtain convergence results under some assumptions, and we prove the existence of common best proximity points for a family of non-self-a-nonexpansive mappings.